High Proportion of Active Nitrogen‐Doped Hard Carbon Based on Mannich Reaction as Anode Material for High‐Performance Sodium‐Ion Batteries. Issue 7 (8th February 2023) - Huang, Gang; Kong, Qingquan; Yao, Weitang; Wang, Qingyuan
Abstract: The potential for energy storage in carbonaceous materials is well known. Heteroatom doping – particularly nitrogen doping – can further enhance their electrochemical performance. The type of N configuration determines the reactivity of doped carbon. It remains a challenge, however, to achieve a high ratio of active N (N‐5) in N‐doped carbon. In this study, a high proportion of active nitrogen‐doped hard carbon (PTA‐Lys‐800) is synthesized by the classical Mannich reaction, using tannic acid (TA) and amino acid as precursors. For sodium‐ion batteries (SIBs), PTA‐Lys‐800 provides outstanding cycling stability and rate performance (338.8 mAh g −1 at 100 mA g −1 for 100 cycles, a capacity retention of 86 %; 131.1 mAh g −1 at 4 A g −1 after 5000 cycles). The excellent performance of PTA‐Lys‐800 is attributed to stable hierarchical pore structure, abundant defects, and a high proportion of N‐5 formed during the carbonization process. Based on a detailed fundamental analysis, the pseudocapacitance mechanism is found to contribute to the higher sodium storage process in PTA‐Lys‐800. The Na‐adsorption mechanism is further explored through ex situ Raman spectroscopy. A new method is presented for designing carbonaceous anode materials with high capacity and long cycle life. Abstract : Hard times : A high‐proportion active N‐doped hard carbon (PTA‐Lys‐800) is synthesized by Mannich chemistry. The PTA‐Lys‐800 anode displays excellent storage capability for Na + . As a result of this work, a new method is presented for designing carbonaceous anode materials with high capacity and long cycle life.